1969
DOI: 10.1590/s0037-86821969000200001
|View full text |Cite
|
Sign up to set email alerts
|

Esquistossomose mansoni no estado da Guanabara: aspectos epidemiológicos relacionados às migrações internas

Abstract: Ã lo io S u a s s i i iu i e J . R o d r i g u e s ( o u r a O p re se n te tra b a lh o é o re su lta d o do estu d o e p id em io ló g ico de 2 416 casos de esq u isto sso m o se m a n s o n i observados n a cid a d e do R io de Ja n eiro , E sta d o da G u a n a b a ra , e n tre os anos de 1960 e 1968. Os p a c ie n te s era m o rig in á rio s de 275 m u n ic íp io s de 18 E sta d o s n o B rasil e p o d e-se su p o r qu e s e ja m "in d ica d o res" da d o en ç a nos locais de on d e p ro v ie ra m (desde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1970
1970
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The results of the coproscopical survey in Rio de Janeiro also indicate that appreciable transmission is continuing in the localities of Alto da Boa Vista and Vargem Grande, since both localities have been recognised as low transmission sites (Suassuna & Coura 1969). In contrast with the latter two localities, Santa Cruz transmission has been reducing after intervention carried out by the local health authorities.…”
Section: Gundlachia Ticagamentioning
confidence: 87%
“…The results of the coproscopical survey in Rio de Janeiro also indicate that appreciable transmission is continuing in the localities of Alto da Boa Vista and Vargem Grande, since both localities have been recognised as low transmission sites (Suassuna & Coura 1969). In contrast with the latter two localities, Santa Cruz transmission has been reducing after intervention carried out by the local health authorities.…”
Section: Gundlachia Ticagamentioning
confidence: 87%
“…Accelerating migration from the countryside to cities threatened to overwhelm existing water and sanitation systems, and to increase urban schistosomiasis (Suassuna & Coura 1969, Sturrock 2001. In Brazil outbreaks of acute schistosomiasis, especially in urban areas, were observed and documented with a certain frequency (Ferreira et al 1960, 1966, Coura et al 1970, Neves 1992, Rabello 1995, Barbosa et al 2001.…”
mentioning
confidence: 99%
“…Several studies carried out in Brazil have speculated on the possible causes of the higher or lesser severity of schistosomiasis in the country. Studies on patients from 18 Brazilian States showed a wide variation in the severity of the disease from one region to the other (Suassuna and Coura, 1969;Coura et al, 1974Coura et al, , 1982. These observations were also made in a comparative study between two rural regions, subdivided in two areas in Brazilian Southeast and another two in Brazilian Northeast (Coura et al, 1983).…”
Section: Introductionmentioning
confidence: 66%